2016
DOI: 10.1097/01.aoa.0000504717.83591.ee
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hypertensive Disorders of Pregnancy and Later Risk of Cardiomyopathy

Abstract: (JAMA 2016;315(10):1026–1033) Hypertensive disorders of pregnancy (HDP), including preeclampsia and gestational hypertension, are common, occurring in approximately 10% of parturients worldwide. Women with preeclampsia have been shown to be at increased risk for peripartum cardiomyopathy as well as cardiovascular disease later in life. It has not yet been determined if these women are also at greater risk for developing cardiomyopathy beyond the peripartum period. However, recent research has suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is known that certain pregnancy complications beget further comorbidities: for example, hypertensive disorders of pregnancy can be risk factors for PPCM(14). Overlap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that certain pregnancy complications beget further comorbidities: for example, hypertensive disorders of pregnancy can be risk factors for PPCM(14). Overlap.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data from a Danish nationwide register–based cohort demonstrated that specific subtypes of HDP (i.e. severe preeclampsia, moderate preeclampsia and gestational hypertension) conferred differing risks of incident cardiomyopathy(14). Still, prior studies have not fully elucidated the independent risks of PPCM and HDP subtypes on specific CVD outcomes [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In a 50-year follow-up study, an association between pre-eclampsia and cardiovascular mortality was confirmed (54). Data from the National Patient Register and the National Birth Register in Denmark have shown a small but significant increased risk of cardiomyopathy in women with a history of hypertensive disorders in pregnancy (compared with normotensive women) more than 5 months after delivery (55). A more recent analysis of the nationwide Danish register data found the risks of peripartum cardiomyopathy significantly higher in women with hypertensive disorders in pregnancy and with pre-eclampsia in particular (56).…”
Section: Long-term Cardiovascular Consequences Of Gestational Hypertensionmentioning
confidence: 99%
“…39, 40 Remarkably, Behrens et al reported that women with a history of hypertensive disorders during pregnancy, compared with those without such a history, had a small but statistically significant increased risk of cardiomyopathy more than 5 months after delivery, in a Danish nationwide cohort. 41 In the study, compared with women with normotensive pregnancies (7.7/100,000 person-years), women with a history of hypertensive disorders during pregnancy had significantly increased rates of cardiomyopathy (cardiomyopathy events among women with severe preeclampsia; 15.6/100,000 personyears, among women with mild preeclampsia; 14.6/100,000 person-years, among women with gestational hypertension; 17.3/100,000 person-years). Only half of them were complicated with hypertension when they were diagnosed with cardiomyopathy.…”
Section: Disclosuresmentioning
confidence: 99%